American immanence : democracy for an uncertain world - Hogue, Michael S. (Insurrections., 2018)
The Anthropocene marks the age of significant human impact on the Earth's ecosystems, dramatically underscoring the reality that human life is not separate from nature but an integral part of it. Culturally, ecologically, and socially destructive practices such as resource extraction have led to this moment of peril. These practices, however, implicate more than industrial and economic systems: they are built into the political theology of American exceptionalism, compelling us to reimagine human social and political life on Earth. American Immanence seeks to replace the dominant American political tradition, which has resulted in global social, economic, and environmental injustices, with a new form of political theology, its dominant feature a radical democratic politics. Michael S. Hogue explores the potential of a dissenting immanental tradition in American religion based on philosophical traditions of naturalism, process thought, and pragmatism. By integrating systems theory and concepts of vulnerability and resilience into the lineages of American immanence, he articulates a political theology committed to democracy as an emancipatory and equitable way of life. Rather than seeking to redeem or be redeemed, Hogue argues that the vulnerability of life in the Anthropocene calls us to build radically democratic communities of responsibility, resistance, and resilience. American Immanence integrates an immanental theology of, by, and for the planet with a radical democratic politics of, by, and for the people.